2013
DOI: 10.1088/0029-5515/53/5/053013
|View full text |Cite
|
Sign up to set email alerts
|

Impact of arcing on carbon and tungsten: from the observations in JT-60U, LHD and NAGDIS-II

Abstract: Arcing is a long-standing plasma-surface interaction issue, and the issue is currently being revived. This paper assesses the impact of arcing in fusion devices based on the observations in JT-60U, the Large Helical Device (LHD) and the linear divertor simulator NAGDIS-II. To investigate the first initiation process of arcing, field emission currents from several tungsten samples are measured. It is shown that the field emission current increases significantly after tungsten is exposed to helium plasmas. A pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 34 publications
0
23
1
Order By: Relevance
“…It should be noted that no other significant arc trails were observed on the surface made of SS in the FIDA diagnostic system and pre-installed materials including SS of first walls. There were some reports indicating the evidence that the LHD GDC initiated arcing on ECH and ECE mirrors [3,5]. However, the arcing damage observed in the present study shows a larger area than the previous reports during the brief GDC of 43 hours in total.…”
contrasting
confidence: 79%
“…It should be noted that no other significant arc trails were observed on the surface made of SS in the FIDA diagnostic system and pre-installed materials including SS of first walls. There were some reports indicating the evidence that the LHD GDC initiated arcing on ECH and ECE mirrors [3,5]. However, the arcing damage observed in the present study shows a larger area than the previous reports during the brief GDC of 43 hours in total.…”
contrasting
confidence: 79%
“…3 Recent studies have shown that transient heat loads on the divertor, such as Edge Localized Modes (ELMs), might trigger unipolar arcing, and that fuzz significantly increases its ignition. 4 The existence of the unipolar arc has been confirmed phenomenologically by erosion craters found in numerous fusion devices: JT-60U, LHD, 5 DIII-D, 6 and ASDEX Upgrade. 7,8 Moreover, since the arcing may take place in fusion experiments, special model experiments have been conducted for a systematic study in which arcing is initiated by plasmas generated by a high-frequency discharge, 9,10 a plasma gun, 11,12 and a laser beam.…”
Section: à3mentioning
confidence: 94%
“…On the other hand, the presence of the fuzz raises the possibility of another issue, ignition of unipolar arcing. So far, the arcing in fusion‐relevant devices has been reported in: JT‐60U, LHD, ASDEX‐U, and DIII‐D . Arc ignition is harmful to fusion devices because it can be a cause of erosion of PFC and an impurity source to a core plasma .…”
Section: Introductionmentioning
confidence: 99%